Acute Cutaneus Lupus Erythematosus in a Welder: a Case Report - Soemarko, Dewi S.; Asep (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: Cutaneous Lupus Erythematosus (CLE) is a diverse group of autoimmune connective tissue disorders localised to the skin that can be associated with Systemic Lupus Erythematosus (SLE). Chronicity and recurrency of this disease can cause a significant reduction in worker productivity, absenteeism and medical expensesObjective: To identify Cutaneous Lupus Erythematosus in welder is an occupational diseases or work aggravated diseases which will be implemented through seven step of ocupational disease.Case Presentation: A 42-year-old patient came with complaints of red patches on the face, scalp, and hands since 3 months ago. the patient was previously treated at an internal medicine polyclinic and was diagnosed with SLE. The patient was then referred to the dermatology department of allergy and immunology and was diagnosed with acute cutaneous lupus erythematosus.Discussion: According to the PERDOKI’s seven step guideline to diagnosis occupational disease, in this patient is declared as work aggravated disease. UV light is a major environmental triggering or precipitating factor in cutaneous lupus erythematosus(LE). Avoiding or reducing UV light exposure from the sun and from work are essential to prevent recurrence.